Natural recovery from long-lasting generalised dissociative amnesia and of cerebral blood flow. Issue 12 (11th December 2019) - Mitsui, Nobuyuki; Oyanagi, Yuka; Kako, Yuki; Kusumi, Ichiro
Abstract : A 40-year-old man presented with generalised dissociative amnesia. At 2 weeks after onset, N-isopropyl-[ 123 I] p -iodoamphetamine-single-photon emission CT imaging of the brain revealed hypoperfusion in the right medial temporal area. Organic brain damage was ruled out. His inability to recall information was attributed to psychological stress related to his employment. Consistent with this diagnosis, his generalised dissociative amnesia lasted 6 years and 10 months; however, he recovered from amnesia naturally on starting a new job. Perfusion of his right medial temporal area also returned to normal levels. Longitudinal reports for generalised dissociative amnesia with natural recovery are exceedingly rare. It is important to confirm whether dissociative amnesia and cerebral blood flow recover in parallel, even in cases where dissociative amnesia is long-lasting.